2010
DOI: 10.1200/jco.2009.26.3814
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Gene–Negative Alveolar Rhabdomyosarcoma Is Clinically and Molecularly Indistinguishable From Embryonal Rhabdomyosarcoma

Abstract: The clinical behavior and molecular characteristics of alveolar cases without a fusion gene are indistinguishable from embryonal cases and significantly different from fusion-positive alveolar cases. This implies that fusion gene status irrespective of histology is a critical factor in risk stratification of RMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
389
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 428 publications
(435 citation statements)
references
References 28 publications
33
389
2
Order By: Relevance
“…It is interesting to note that we consistently found that gene expression profiles of fusion gene-negative ARMS closely resembled that of ERMS. This is in line with recent reports that ARMS cases lacking PAX3/7-FOXO1 chromosomal translocations are indistinguishable in their gene expression profiles from ERMS (Davicioni et al, 2009;Williamson et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It is interesting to note that we consistently found that gene expression profiles of fusion gene-negative ARMS closely resembled that of ERMS. This is in line with recent reports that ARMS cases lacking PAX3/7-FOXO1 chromosomal translocations are indistinguishable in their gene expression profiles from ERMS (Davicioni et al, 2009;Williamson et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Myf5 is regulated by Hh signaling (Gustafsson et al, 2002;Gerber et al, 2007). Initially, we assessed expression profiles of these markers in a group of 103 RMS patients that we recently characterized (cohort 1) (Williamson et al, 2010). In addition, we analyzed a previously published separate group of 132 RMS patients to validate our results (cohort 2) (Davicioni et al, 2006).…”
Section: Hh Pathway Activation In Rms Subtypesmentioning
confidence: 99%
See 3 more Smart Citations